Mediation Roles of Transformational Leadership andPsychological Empowerment on Work-Life Balance and In-role Performance of Vocational Educators in Nigeria - Nathaniel Ifeanyi Edeh; Ezebuiro, Felicia N.; Agnes Lawrence Okute; Calister Lebechukwu Nwadi; Emeka Promise Ugwunwoti (Journal of Technical Education and Training, 2024)
This study is necessitated by the dire need to determine the mechanisms of leadership transformation approaches that explain why 360-degree feedback is effective in helping supervisors and subordinates identify weaknesses and strengths and take positive actions for institutional health, growth, and productivity. The study ascertained whether transformational leadership and psychological empowerment jointly mediate work-life balance and vocational educators’ in-role performance in Nigeria’s TVET institutions. The study tested several hypotheses based on survey responses from 754 TVET stakeholders (Deans, HODs, educators, undergraduate and postgraduate students). Data was elicited from the participants using four Scales(Transformational Leadership, In-role Performance, Psychological Empowerment, and work-life balance Questionnaires). The reliability of the instruments was determined using the Cronbach alpha technique. At the preliminary level, data collected were analysed using descriptive and inferential statistics. The hierarchical Multiple Regression method was employed to test the hypotheses and to determine the total, direct and indirect effects of the variables studied. The result indicated that psychological empowerment and work-life balance jointly and significantly mediated the relationship between transformational leadership and the in-role performance of vocational educators. Similarly, a positive significant association exists between psychological empowerment and educators’ in-role performance. This study contributes to the extant literature on quality management theory by contributing to strategies that promote supervisors’ transformational leadership styles, vocational educators’ in-role performance, and work-life balance. The practical implications for institutional practitioners and researchers, limitations, and suggestions for future research were discussed.